If You're Reading This, It's Too Late - Bosch, Pseudonymous (United States Little, Brown Books for Young, 2008)
If You're Reading This, It's Too Late is the second installment in Pseudonymous Bosch's Secret Series, following 12-year-old survivalist Cass and her friend Max-Ernest. As new members of the Terces Society, they must find a 500-year-old man-made man (homunculus) before the evil Midnight Sun group, led by Ms. Mauvais and Dr. L, uses him to gain immortality.
English
Keywords: Mystery; Adventure